Characteristics of tuberculosis patients at intake in Cambodia, two provinces in China, and Viet Nam - Lauritsen Jens M; Sokun Chay; Wei Chen; Hoa Nguyen B; Rieder Hans L (BMC, 2011)
Abstract Background The tuberculosis register is a critical data source for the information system of national tuberculosis control programs. From the information in the tuberculosis case register, it is possible to extend the standard analysis of age and sex characteristics among sputum smear-positive cases to all tuberculosis case categories. National tuberculosis programs might utilize such information to identify problems related to referral and access to diagnosis and treatment. Objectives Based on the electronic database we created, our objectives were to provide a detailed description of age and sex characteristics of tuberculosis patients at registration and to provide a comparison of age-specific sex characteristics among incident and prevalent sputum smear-positive cases. Methods A representative sample of tuberculosis case registers from 1 January 2003 to 31 December 2005 was selected in Cambodia, two provinces in China and Viet Nam. Age and sex characteristics of cases in the three separate prevalence surveys in the three jurisdictions (Cambodia: year 2002; China: year 2000; and Viet Nam: year 2006-2007) were obtained for comparison. Results A total 37,635 patients had been registered during the period in the selected units in the three countries. Cases were more frequently male in all three countries with 53%, 71%, and 69% in Cambodia, China, and Viet Nam, respectively. The ratios of the female-to-male odds in the notification system to that in the prevalence survey in smear-positive cases in Cambodia, China and Viet Nam were 2.1, 0.9, and 1.8, respectively. Because of the small proportion of extrapulmonary tuberculosis registered in China, we limited the analysis on age and sex distribution for extrapulmonary cases to Cambodia and Viet Nam. The proportion with extrapulmonary tuberculosis among all cases was 18.5% in Cambodia and 15.7% in Viet Nam, decreasing in frequency with increasing age. Conclusions Characteristics of patients greatly differed between countries and between patient categories. In Cambodia and Viet Nam, efforts should be made for improved case-finding of sputum smear-positive tuberculosis among males.